PENGARUH KINERJA PEGAWAI TERHADAP PENINGKATAN PELAYANAN MASYARAKAT DI LINGKUNGAN DINAS TATA RUANG KABUPATEN KUTAI TIMUR - Swarni Marwan (ADMINISTRASI PUBLIK, 2017)
This study is intended to determine the effect on the improvement of the performance of public services in the district spatial East Kutai, therefore the researchers to formulate hypotheses "Anticipated performance of employees have an influence on the improvement of services to the community in the district spatial Kutai Timur".The timing of the research was conducted in August 2016 until November 2016 for 3 (three) months. The research method in this study is quantitative, the data obtained through direct observation in the field and distributing questionnaires to the interviewees by the number of samples which are 21 (twenty one) respondents.Based on the calculation simple regression analysis known there is a correlation between the performance of the service improvement with the number 0.822 employees. This figure is interpreted as a very strong correlation between the performance of the employee service improvement.While testing the hypothesis generate a number of performance variables thitung = 4.079, significant at the 0.004 level, this means that the variable performance of employees is statistically very significant influence on community service for 0.004 <0.05. Thus it can be said that there is a positive relationship between the variables of performance (X) and the service variable (Y) employees in the Department of Spatial Planning of East Kutai.